La investigación de las prácticas sociales y culturales de justicia (2018)
This article relates the investigation task and the theoretical and methodological reflections that had faced the Investigation Center and the typical difficulties of the investigation practice. It picks up briefly the experiences of the practice of teaching connected with investigation and presents a description of the theories and methodologies specifying some of the challenges that faces the socio juridical investigation at present.